An Analysis of Students' Problems in Writing a Research Proposal - Afifa Rastri; Yanti Sri Rezeki; Urai Salam; Dwi Riyanti; Surmiyati Surmiyati (Acitya: Journal of Teaching and Education, 2023)
This research aimed to determine undergraduate students’ problems and factors causing the problems in writing a research proposal. Ninety-one English Education Study Program undergraduate students in FKIP Universitas Tanjungpura, Pontianak, West Kalimantan, participated in this research. This descriptive research used forty items in a questionnaire as the instrument modified from Dwihandini, Marhaeni, and Suarnajaya’s (2013) model. The model utilized three factors causing students’ problems in writing a research proposal, namely (1) psychological factors, (2) socio-cultural factors, and (3) linguistic factors. To report the findings of the results, the researcher used the descriptive statistics technique to display each factor's percentage score. The findings indicated that the score of linguistic factors got the highest (75,49%), which highly affected students' writing in research proposals. The conclusion is each factor causes problems, so it affects students in writing a research proposal, and linguistic factors become the dominant factor among others.